(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The problem of sexual harassment of women is one of the largest and most dangerous social problems that all countries of the world suffer from, and which they strive to combat, especially after its widespread spread in the current situation in light of crises and wars, and the resulting health, social and psychological damages that are reflected on women, as it is a phenomenon that affects the construction of society and its individuals socially and psychologically. In this context, this study seeks to identify the most important theoretical trends that have addressed the phenomenon of sexual harassment of women. Due to its serious consequences on individuals, families and society, which imposes on researchers, scholars and workers in the social, educational and legal fields alike to intensify efforts to address this phenomenon and reduce it as much as possible. The descriptive approach was adopted, followed by some recommendations and proposals to reduce the phenomenon of sexual harassment. The study aims to determine the prevalence of sexual harassment among female university students in the age of digital media and the influence of social networks and pornography. This study was conducted on 233 female students in colleges across the United States and utilized a descriptive approach. The findings revealed that sexual harassment occurs at a rate of 44.4% in universities, with one of the contributing factors to such harassment being the consumption of pornography. In the context of the social concept of harassment, a study by the Egyptian Center for Human Rights defines harassment as "a deliberate sexual act by the harasser that is unwanted by the victim, causing psychological, sexual, physical, or moral harm. This can occur in various settings, including work, public spaces, transportation, educational institutions, or private places such as homes or within family circles.”